Aplikasi Etika dalam Sejarah Politik Umat Islam - Susmihara Susmihara (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
The implementation of the values of Islamic politic ethics by the government in the early Islam contributed to the formation of civic societies. On the contrary, the governance which is not based on Islamic politic ethics will mire its people in misery. Islamic politic ethics is universal, which can be applied on all society without being influenced by place and time. Therefore, Islamic politic ethics are closely related to the basic human right and obligation as well as between state with citizen. The politics in its implementation is aimed at protecting and providing welfare its people, including non Moslem, beside it is also aimed at obeying the law of Allah. Government is in charge of teaching and forming good moral, attitude and behaviour to its society.